The cannabis gardener : a beginner's guide to growing vibrant, healthy plants in every region - Barthel, Penny 1965-; Scott, Erin (California : Ten Speed Press, 2021)
Cannabis is as easy to grow as a tomato plant. If you live in a suitable climate and provide sun, water, and good soil, you can grow vigorous, beautiful cannabis in pots, raised beds, or your own yard. Not only is cannabis an easy addition to your garden, it can also provide health and mood-lifting benefits. The Cannabis Gardener teaches you how to choose which strains are right for you and how to cultivate the plants from seed to finished flower. Gorgeous full-color photographs capture each stage of the growing process and show how cannabis plants can be incorporated into your garden design as well as raised beds and containers. After you establish your plants in the garden and monitor them through the flowering stage, you'll find tips on how to harvest, dry, cure, and store your grow. Also included are recipes for savoring your harvest, from salves, tisanes, and tinctures to cannabutter for baking and cooking delicious treats such as CBD gummies flavored with vanilla beans, cheddar crackers, and even cannabis chocolate sauce."--
Choosing the right cannabis for you and your garden -- Designing your garden space with cannabis -- The four elements: sun, soil, airflow, and water -- The vegetative stage: from seed to teen -- The flowering stage: from blossom to bud -- Harvest preparation: ideas for harvest, setting up your drying space, and evaluating ripeness -- Time to harvest: trimming, drying, curing, and storing your grow -- Savoring your grow: tincture, concentrate, cannabutter, and tisane with key recipes.
Includes index.
Also issued in electronic format.
110592
Keywords: Cannabis; Gardening; Cannabis -- Seedlings -- Growth; Cannabis -- Plants -- Harvesting; Gardening